Effects of Temperature on Colour of Selected Pig Organs in Silicone (S10) Plastination - Akhter, Tahmina; Molla, Mizanur Rahman; Alam, Mahbub; Akhter, Tahmida; Akhond, Farjana; Afroze, Sadia Nure (International Journal of Human and Health Sciences (IJHHS), 2021)
Background: Temperature is one of the most important factors that are responsible for plastination procedure. Objective: The present study was designed to determine a suitable method of plastination of skeletal muscle in a low-resource setting in Bangladesh. Methods: This observational study was carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, between March 2015 and February 2016. Six whole pig kidneys (as firmer organ) and six whole pig lungs (as softer organs) were collected from a government authorized slaughterhouse in Dhaka city. Same numbers of organs were designated as ‘Cold Temperature Group’ and ‘Room Temperature Group’. We observed the change in colour at cold and room temperatures after different stages of plastination with a colour chart. Results: After fixation, both the brownish kidneys and reddish pink lungs turned brownish and darker. After dehydration, both the kidneys and lungs got paler. After forced impregnation, the colour turned much darker in both groups. The colour change continued towards a darker tone with time. The specific colour changes quantified into frequencies were very variable in both temperature groups. Conclusion: In observed colour changes, the difference was indeterminate. International Journal of Human and Health Sciences Vol. 05 No. 03 July’21 Page: 324-329